Changes in the stomatognathic system in face of COVID-19 - an integrative review - Taques, Luana; Carlos Bortoluzzi, Marcelo; Carla Karpinski, Bruna; Brigola, Sabrina; Cristina de Mattos, Jéssica; Rodachinski, Paulyne (Seven Editora, 2023)
The oral cavity is closely related to SARS-CoV-2 due to the high concentration of angiotensin-converting enzyme 2 receptors. In addition, the infection and its associated therapies contribute to the manifestation of oral changes in different cases. The purpose of this research was to conduct a review regarding the possible changes that SARS-CoV-2 causes in the stomatognathic system. The methodology used was an integrative literature review, guided by the research question developed by the PICO strategy. The results showed that the main oral changes associated with COVID-19 are disorders of taste and smell, followed by dry mouth or hyposalivation and ulcerations. Several oral manifestations have been observed, however, there is not enough evidence to determine a causal relationship with infection or SARS-CoV-2. It is important that health professionals are aware of dysgeusia and hyposmia as the first sign of COVID-19. DOI: 10.56238/pacfdnsv1-019